2016
DOI: 10.11604/pamj.2016.24.104.8301
|View full text |Cite
|
Sign up to set email alerts
|

Tumeur pseudopapillaire et solide du pancréas: à propos d’un cas et revue de la littérature

Abstract: Les tumeurs pseudopapillaires et solides du pancréas sont des tumeurs rares, d’étiopathogénie encore incertaine, et surviennent surtout chez la jeune femme. Leur pronostic reste bon surtout après exérèse complète. Nous rapportons une nouvelle observation d'une jeune femme, révélée par des douleurs abdominales. Le diagnostic est porté sur l’étude histologique associée à l'immuno-histochimie de la pièce de spléno-pancréatectomie caudale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…It is a rare tumor and represents 0.3% -2.7% of pancreatic tumors [1]. In the literature, most authors have reported isolated cases [6] [7] [8]. According to Papavramidis T in 2005, about 718 cases were reported in the English literature, and these were mostly isolated cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare tumor and represents 0.3% -2.7% of pancreatic tumors [1]. In the literature, most authors have reported isolated cases [6] [7] [8]. According to Papavramidis T in 2005, about 718 cases were reported in the English literature, and these were mostly isolated cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…8 O uso de quimioterapia ou radioterapia adjuvante mantém-se questionável. 9 Os tumores sólidos pseudopapilares têm curso indolente e crescimento lento, com taxa de mortalidade inferior a 2%. 1 Cerca de 85% dos doentes apresentam doença localizada ao diagnóstico, sendo que 10%-15% têm doença disseminada, sobretudo nos gânglios linfáticos, fígado, baço, cólon, e mesocólon.…”
Section: Discussão/conclusãounclassified
“…1 Cerca de 85% dos doentes apresentam doença localizada ao diagnóstico, sendo que 10%-15% têm doença disseminada, sobretudo nos gânglios linfáticos, fígado, baço, cólon, e mesocólon. 9 Quando a ressecção é completa, o prognóstico a longo prazo é excelente, com taxa de sobrevida aos 5 anos de 95%. 7 Recomenda-se follow-up, para monitorizar possível recidiva local ou metástases a distância.…”
Section: Discussão/conclusãounclassified
“…For the clinical investigation of Frantz Tumor, laboratory tests are of little significance. It is also noteworthy that tumor markers are of little diagnostic aid, as they are rarely altered (occasionally there are minimal elevations in CA19-9), in addition to the absence of alterations in pancreatic or canalicular enzymes 7,8 .…”
Section: Laboratory Testsmentioning
confidence: 99%